Analyzing Bacterial Agents of Keratoconjunctivitis in Patients Referred to Ophthalmology Ward of Feiz Hospital in Isfahan - Noushin Sohrabi; Majid Tebianian; Heidarali Moeini (Fasa University of Medical Sciences, 2011)
Background & Objectives: Keratoconjunctivitis is considered as the most prevalent ocular disease which is caused by multiple microorganisms. Considering the fact that identifying etiologic agents of Keratoconjunctivitis in a specific geographical area, and determining their antibiotic resistance pattern could be very important in specifying treatment strategy of such patients, the present research has been conducted to discriminate and evaluate etiologic microbial agents of this disease in patients referred to ophthalmology ward of Feiz health center in Isfahan. Materials & Methods: This descriptive study has been conducted in an 18-month period on 196 patients, referred to ophthalmology ward of Feiz hospital with positive symptoms of Keratoconjunctivitis. Ocular secretions were sampled with sterile swap and from conjuctival sac. Then the related samples were transferred and cultured in the medium for bacteria. Antibiogram of isolated strains was performed by method of disc diffusion. One of the samples related to patients was transferred to virus transport media and was used for direct immunofluorescence test. The possible content of IgM anti-adenovirus was investigated by ELISA method and on serum samples of patients. Resulst: From among the total 196 evaluated samples, 75 cases were infected with bacterial agents, 37 cases with adenovirus, and 58 cases with both bacterial and adenovirus agents. The isolated bacterial agents were as follows with respect to their prevalence, Staphylococcus aureus (28.1%), Coagulase negative Staphylococci (16.8%), Bacillus spp (6.6%), Pseudomonas aeruginosa (5.1 %), Enterobacter (4.2%), Klebsiella (3.6%) and Streptococcus group D (3.6%). From among antibiotic drugs, the highest rate of sensitivity for S. aureus and P. aeruginosa was observed in Ciprofloxacin and Tobramycin respectively. Conclusion: The results of the study could be applied in specifying treatment strategies for patients suffering from Keratoconjunctivitis in Isfahan city.